APLIKASI SISTEM PAKAR UNTUK MENDETEKSI KERUSAKAN PADA PRESSURE TRANSMITER ROSEMOUNT 1151 DENGAN METODE FUZZY - Masagus Mochammad Yusuf (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2016)
System information on hardware prediction damage expert system transmitter with fuzzy method is a system, that aims to help the workers in prediction the damage and estimate the age of the equipment. So that workers will be easy to find a replacement tool in accordance defect with and time is not wasted. The information system is based desktop using java programming language and editor using Net beans 7.4, Using MySQL database and XAMPP as database design, data processing easier for workers. The author realizes there are still many shortage in limitation in making a prediction expert system hardware defect the transmitter and author limit where only the employees concerned are entitled to complete the problem. Keywords: Expert System defect detection, KMI, Fuzzy, Pressure Transmitter Rosemount Type 1151.